The Influence of Reproduction Media and Animation Videos on Knowledge and Attitudes Regarding Reproduction and Sexuality in Elementary School Students - Vivi Silawati; Frenta Helena Simaibang; Azzahroh, Putri (Rajaki of Tulip Medika Publisher, 2023)
Background: Sexual violence in children occupies the highest position, 50% -62%. The Indonesian Child Protection Commission (KPAI) released that in early 2018, there was 117 sexual violence against children, while in 2017, there were 393 cases in Schools plays an important role in increasing students' knowledge and sexual education. So far, sex education has been implemented only with the introduction of reproductive organs, forms of violation, danger and impact. Furthermore, the children try to find other knowledge to satisfy their curiosity. Purpose: To determine the effect of media flipcharts and video animation on knowledge and attitudes about reproduction and sexuality in elementary school students. Method: Experimental research with one group pretest-posttest design in which the design consisted of one group then observed (pretest), after which intervention was given in the form of counselling using flipchart media and animated video and then observed again (posttest). Result: difference test in two measurements paired-samples T-Test which showed the average of students' knowledge before giving information about reproduction and sexuality using flipchart media and animated videos on students, which was an average of 7.72 and the average after a given intervention to 10.64. While the attitude of students before being given information about reproduction and sexuality by using the media flipchart and animated video is an average of 32.96, and after being given an intervention, the average becomes 35.34. Conclusions: It was concluded that the media of flipcharts and animated videos influence knowledge and attitudes about reproduction and sexuality in elementary school students. Thus, the school is advised to provide reproductive and sexual education by applicable norms and can use flipcharts and animated videos.